Development of a Model for Calculating the Slip Coefficients of a Mechanical Wheeled Vehicle with Two Steering Axles - Bekenov, Tassybek N.; Nussupbek, Zhanibek T.; Tassybekov, Zhandos T.; Sattinova, Zamira K. (Communications - Scientific Letters of the University of Zilina, 2022)
The purpose of the study is to perform appropriate calculations of the values of the total slip coefficients alternately on the sides of a vehicle, depending on the angles of rotation of its axles, using the single slip coefficients of its individual wheels directly when turning. The basis of the methodological approach in this study is a combination of system analysis of the principles of calculating the slip coefficients of a mechanical wheeled vehicle with an analytical investigation of problematic aspects of developing a model for calculating the slip coefficients of a vehicle with two steering axles. The results obtained indicate the presence of a persistent relationship between the slipping coefficients of a mechanical wheeled vehicle and the rotation angles of its two steering axles, including a number of other parameters that are important from the standpoint of traffic safety.
Keywords: mechanical wheeled; vehicle; steering axle; complex slipping coefficients; model for calculating slipping coefficients; slipping of a mechanical wheeled vehicle